Integrating Communication Strategies in Mathematics Education: A Qualitative Study in Medan, Indonesia - Thariq, Muhammad (Indonesian Journal of Education and Mathematical Science, 2025)
This qualitative research investigates the integration of communication studies into mathematics education in Medan, Indonesia, focusing on the impact of interdisciplinary teaching strategies on student engagement teaching strategies on student engagement and understanding. Through semi-structured interviews and classroom observations, the study examines how mathematics educators in secondary schools incorporate communication techniques, such as visual aids, storytelling, and collaborative learning, to improve students’ comprehension of mathematical concepts. The results highlight that integrating communication skill not only enhances students’ mathematical literacy but also fosters critical thinking, problem-solving, and teamwork. The findings suggest that such interdisciplinary approaches are especially effective in Medan’s diverse cultural and linguistic environment, offering a model for educational reform in Indonesia and similar multicultural contexts